Gilded-Age Entrepreneurs and Local Notables: The Case of the California “Big Four,” 1861-1877 - Evelyne Payen-Variéras (Transatlantica)
This article proposes an analysis of the network and transactions management practices of the California “Big Four”, the group of former Gold Rush merchants who built the Central Pacific and Southern Pacific Railroad companies in the 1860’s and 1870’s. The associates’ decisions in their dealings with business partners, professionals and politicians in Northern California did not reflect simple alternatives between integration and market transactions as described in the classical Chandlerian synthesis and the mid-twentieth century theory of the firm. The paper highlights the significance of partnership agreements, credit relations and negotiations with local boosters and politicians. It concludes that the “Big Four” did not see credit opportunities and political advantages as alternatives to good management but as important elements of business success, on a par with the pursuit of low operating costs and high earnings.